Long-Term employee illness and frustration of the contract of employment - Guthrie, Rob; Meredith, Frances (Industrial Relations Society of Australia, 2007)
This article considers the issues that arise when a worker becomes incapacitated for work and the contract of employment is put in peril by reason of long-term absence from work. The doctrine of frustration of the contract of employment and its contemporary application is the starting point for discussion. Most typically in the employment context this arises as a consequence of the death or serious injury of the worker. In examining the interaction of these concepts the article examines the contemporary application of the case of Finch v Sayers ([1976] 2 NSWLR 540), which has been influential in the interpretation of the application of the doctrine of frustration of contract in employment matters. In the final section the decision in Finch v Sayers is reconsidered having regard to contemporary influences and changes in labour market regulation. At the time of writing the Workplace Relations Amendment (WorkChoices) Act 2005 (Cth) had only recently been enacted. An additional brief comment on some possible implications for frustration of contract of employment concludes the article.